Proceedings of the 16th Python in Science Conference 2017
DOI: 10.25080/shinma-7f4c6e7-00b
|View full text |Cite
|
Sign up to set email alerts
|

MatchPy: A Pattern Matching Library

Abstract: Pattern matching is a powerful tool for symbolic computations, based on the well-defined theory of term rewriting systems. Application domains include algebraic expressions, abstract syntax trees, and XML and JSON data. Unfortunately, no lightweight implementation of pattern matching as general and flexible as Mathematica exists for Python [Pö16], [Hao14], [Sch14], [Jen15]. Therefore, we created the open source module MatchPy which offers similar pattern matching functionality in Python using a novel algorithm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, the employed discrimination nets come with a one-time construction cost which needs to be amortized to benefit from their speedup. In previous experiments [32], [33], when considering typical numbers of subjects for the respective application, many-to-one matching was always faster overall. Therefore, many-to-one matching is likely to result in a compelling speedup in practice.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the employed discrimination nets come with a one-time construction cost which needs to be amortized to benefit from their speedup. In previous experiments [32], [33], when considering typical numbers of subjects for the respective application, many-to-one matching was always faster overall. Therefore, many-to-one matching is likely to result in a compelling speedup in practice.…”
Section: Discussionmentioning
confidence: 85%
“…multiprocessing or dask), the experiments do not cover this. We do not consider the singular setup time for many-to-one matching or code generation here, because previous experiments have shown that the setup time is easily amortized [32], [33].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, no lightweight implementation of pattern matching as general and flexible as Mathematica exists for Python. The purpose of MatchPy Krebber, Barthels, and Bientinesi 2017a) is to provide this functionality in Python. While the pattern matching in SymPy (Meurer et al 2017) can work with associative/commutative functions, it does not support finding multiple matches, which is relevant in some applications.…”
mentioning
confidence: 99%